Legal Politics for the Establishment of DKI Jakarta Province Regional Regulation No. 2 Year 2020 about Covid-19 - Rahmat Ilhamdani (IHSA Institute, 2022)
Health is a fundamental and invaluable human right for the implementation of other human rights. Therefore, the right to health should be respected and implemented by the state as one of the fundamental rights. The state's obligation to provide protection for the right to health owned by all citizens is in line with what is stated by WHO, namely the state in this case the government has a responsibility for the health of its citizens. Establishment of Regional Regulation No. 2 of 2020 concerning Covid-19 from the point of view of legal politics is that Law Number 2 of 2020 is the ratification or stipulation of Government Regulation in Lieu of Law Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling the COVID-19 Pandemic and in the Context of Threats That Endanger the National Economy or Financial System Stability into Law.